Sociolinguistic Dimensions of Language Shift and Identity Renegotiation Among Belait Speakers in Brunei Darussalam: Sociopolitical Implications - Zulkiflee, Zulfadzlee; Suhaimi, Elmy Maswandi (Journal of Language and Literature Studies, 2025)
This study investigates the ongoing shift of the Belait language in Brunei and its impact on identity renegotiation among its speakers. The research examines socio-political, cultural, and cognitive factors contributing to language attrition, particularly the dominance of Dialek Melayu Brunei and English. Using qualitative methods, including in-depth interviews and observations, data were analyzed through a sociocognitive framework to explore how Belait speakers navigate linguistic and cultural changes. Findings indicate that intra-marriage plays a crucial role in language preservation, fostering intergenerational transmission and reinforcing cultural identity. Conversely, mixed marriages accelerate the shift toward dominant languages, diminishing the use of Belait within households. Socio-political pressures, including language policies that prioritize Malay and English in education and administration, further marginalize Belait, limiting its functional domains. Additionally, economic influences, such as increased labor migration, contribute to the preference for dominant languages in professional settings. Despite these challenges, community-driven efforts, including familial language practices and cultural initiatives, demonstrate resilience in preserving linguistic heritage. The study highlights the urgent need for comprehensive language policies, educational inclusion, and institutional support to revitalize the Belait language. Addressing structural and attitudinal barriers is essential to sustaining linguistic diversity and strengthening cultural identity within Brunei’s evolving multilingual landscape.